COVID-19 and related social distancing measures induce significant metabolic complications without prominent weight gain in Korean adults - Ko, Hae-Jin; Cho, Yoon Jeong; Kim, Kyoung-Kon; Kang, Jee-Hyun; Kim, Young-Sang; Haam, Ji-Hee; Hur, Yang-Im; Choi, Hye-In; Lee, Kyu Rae; Park, Jung Ha; Cho, Soo Hyun; Kim, Jong-Koo; et al. (Frontiers in Medicine, 2022)
Background: This study using multi-center health examination data from Korean adults was conducted to confirm changes in weight, and their related cardiometabolic parameters, before and after strengthening of social distancing regulations. Methods: A retrospective cohort study was conducted using health check-up data from 13 university hospitals. The study period was from January 2018 to July 2020. To examine the effect of systematic social distancing measures, participants who underwent a health check-up (Visit 3) between July 2020 and July 2021 (during full scale social distancing), and had undergone two previous health check-ups (Visits 1 and 2) between January 2018 and June 2020 (before social distancing), were selected. In total, data from 7,875 participants were analyzed. Linear mixed-effect models were used to calculate estimates of anthropometric indices and metabolic markers measured on Visits 2 and 3, compared with measurements from Visit 1. Results: There were no significant differences in body weight, body mass index, waist circumference, and body composition on Visit 3 than on Visits 1 and 2. However, the odds of metabolic syndrome and its components, including hypertension, high glucose, diabetes, hypercholesterolemia, hypertriglyceridemia, hyper-non-high-density lipoprotein cholesterolemia, and dyslipidemia were significantly higher on Visit 3 than on Visits 1 and 2. The increase in metabolic complications was marked, particularly in relatively young adults who visited health check-up centers located in the capital area. Conclusion: Metabolic syndrome and its components were significantly worse after high level social distancing, although there were no significant increases in anthropometric indices and body fat levels. Healthcare providers need to prevent and manage worsening of metabolic parameters in subpopulations prone to be more sedentary and eat unhealthy food during the COVID-19 pandemic and associated social distancing measures.